The Influence of Financial Literacy on Investment Behavior With Spiritual Attitude and Self-Efficacy as Mediating Variables Among Economics Teachers in Bekasi District - Harlina; Prof.Dr.Saparuddin.M, M,S.i; Dr. Agus Wibowo,S.Pd.I, S.Pd, M.Pd (Journal of Digital Business and Global Economy, 2025)
This research aims to analyze the influence of financial literacy on investment behavior with spiritual attitudes and self-efficacy as mediating variables among social studies teachers in Bekasi Regency. Using a descriptive quantitative approach with 181 respondents through purposive sampling and data analysis using PLS-SEM via Smart-PLS, the results show that financial literacy has a positive and significant impact on investment behavior, both directly and through the mediation of spiritual attitudes and self-efficacy. Financial literacy enhances teachers' ability to manage finances, while spiritual attitudes encourage ethical investment decision-making, and self-efficacy increases the courage to face investment risks. These findings have implications for strengthening social studies learning that integrates financial and moral values, although limited to the context of social studies teachers in Bekasi Regency. There are a maximum of 5 keywords.